PATENT DUCTUS ARTERIOSUS CLOSURE: EXPERIENCE FROM A TERTIARY REFERRAL CENTER - Faim,Diogo Remi Oliveira (2021)
ABSTRACT Objective: To characterize the number and methods of closure of Persistent Ductus Arteriosus (PDA) over a span of 16 years in a third level maternity hospital. Methods: Retrospective study of neonates born between January 2003 and Deccember 2018, who underwent ductus arteriosus closure by pharmacological, surgical and/or transcatheter methods. Gestational age, birth weight, number and methods of closures per year were evaluated. The success rate of the pharmacologic method was calculated, as well as the mortality rate. The association between mortality and birthweight, treatment used and treatment failure was explored. Results: There were 47,198 births, 5,156 were preterm, 325 presented PDA and 106 were eligible for closure (median gestational age - 27 weeks, birthweight <1000 g - 61%). Frequency of PDA closure decreased during the study period, especially starting in 2010. Success rate with pharmacologic treatment was 62% after the first cycle and 74% after the second. After drug failure, 12 underwent surgical ligation and two underwent transcatheter closure. Exclusive surgical ligation was indicated in four infants. Ibuprofen replaced indomethacin in 2010, and acetaminophen was used in three infants. Among the 106 infants, hospital mortality was 12% and it was associated with birthweight <1000 g (13/65 <1000 vs. 0/41 >1000 g; p=0.002) and with failure in the first pharmacologic treatment cycle (13/27 with failure, vs. 0/75 without failure; p<0.001). Conclusions: The national consensus published in 2010 for the diagnosis and treatment of PDA in preterm infants led to a decrease in the indication for closure. Pharmacological closure was the method of choice, followed by surgical ligation. Birthweight <1000 g and first cycle of pharmacologic treatment failure were associated with higher mortality.